2014
DOI: 10.1128/cvi.00643-14
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Immunological Features of the Alpha-Like Proteins of Streptococcus agalactiae

Abstract: bNearly all Streptococcus agalactiae (group B streptococcus [GBS]) strains express a protein which belongs to the so-called alphalike proteins (Alps), of which C␣, Alp1, Alp2, Alp3, Rib, and Alp4 are known to occur in GBS. The Alps are chimeras which form mosaic structures on the GBS surface. Both N-and C-terminal stretches of the Alps possess immunogenic sites of dissimilar immunological specificity. In this review, we have compiled data dealing with the specificity of the N-and C-terminal immunogenic sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
(119 reference statements)
0
37
0
Order By: Relevance
“…111 Certain domains of Alp proteins may display high sequence similarity, which provides a structural basis for their interactions with the same host receptor and cross-protective immunity. 114 The roles of AlphaC and BetaC proteins have been extensively studied, compared with those of the other members of the Alp family. AlphaC protein was shown to be an important ligand involved in the GBS binding to human cervical epithelial cells through its interaction with glycosaminoglycan (GAG).…”
Section: Alp Protein Familymentioning
confidence: 99%
See 1 more Smart Citation
“…111 Certain domains of Alp proteins may display high sequence similarity, which provides a structural basis for their interactions with the same host receptor and cross-protective immunity. 114 The roles of AlphaC and BetaC proteins have been extensively studied, compared with those of the other members of the Alp family. AlphaC protein was shown to be an important ligand involved in the GBS binding to human cervical epithelial cells through its interaction with glycosaminoglycan (GAG).…”
Section: Alp Protein Familymentioning
confidence: 99%
“…Preclinical vaccine investigations of the AlphaC, Alp3, and Rib proteins have been conducted, but the use of Alp proteins as universal vaccines has been limited due to the heterogeneity of the Alp sequence.. 114,[120][121][122][123] Nevertheless, MinervaX Inc. recently reported that the fusion protein of the highly immunogenic N-terminal domains of AlphC and Rib (GBS-NN) led to over 30-fold increase of GBS-NN-specific antibody in their phase I clinical trial with 240 healthy adult women (NCT02459262). 124 Serine-rich repeat proteins Doro et al 125 performed surfome analysis to identify GBS proteins with domains protruding from the bacterial surface.…”
Section: Alp Protein Familymentioning
confidence: 99%
“…Most investigators describe protein similarity in terms of "percent identity" of amino acids whereas E-values and bit-scores are also useful for inferring homology. Non-cross-reacting domains usually show less than 70% sequence identity, emphasizing the genetic basis for immunological specificity (Maeland et al, 2015). McNulty et al (2015) adopted the criterion of 70% amino acid sequence identity over more than 70% of the total protein length for identification of putative diagnostic antigens from Onchocerca volvulus.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…RD2 is present in a small number of other GAS emm types and is >99% identical to a region present in the chromosome of the majority of GBS strains (31). These characteristics suggest that RD2 has been disseminated into different streptococcal strains and species by horizontal gene transfer and recombination (32,33); published data support this idea (33). The presence of RD2 in GBS and emm28 GAS strains causing infections associated with the female genital tract also suggests that genes located on this ICE element are causally involved in this clinical phenotype.…”
Section: Introductionmentioning
confidence: 97%
“…containing the LPXTG consensus sequence that serves to attach these proteins to the cell wall (24,28,32,47,48) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%